The Uncertain Colombian Economic Growth (2017)
One of the most important economic policy objectives in any country is economic growth. Its importance is that if production increases, incomes will be higher tomorrow and future generations will reach higher levels of material welfare. Similarly, if the economy grows - keeping the tax structure constant-, the Government will obtain higher tax revenues and, therefore, will have more resources to finance higher social spending and, thus, fight poverty and satisfy a series of basic needs. Likewise, if the economy grows, productive resources are better exploited and consequently the level of employment increases.